P3.198 Prevalence and correlates of depression among hiv-positive patients in bihar, india: a cross-sectional study. (8th July 2017) - Hussain, Salman; Devi, Nagita; Gupta, Ashok Kumar; Azharuddin, Md
Abstract : Introduction: Depression is accounted as one of the major contributors towards the neuropsychiatric complication among person living with HIV. Depression leads to the non-compliance and accounted for the worst outcomes. So, this study was aimed to assess the prevalence and correlates of depression. Methods: This was a cross-sectional study conducted at the Anti-retroviral therapy (ART) centre, RMRIMS, Patna, India. The study protocol was approved by the institutional ethics committee of Rajendra Memorial Research Institute of Medical Sciences (RMRIMS), Patna (04/RMRI/EC/2016). Patients were interviewed with the Patient Health Questionnaire (PHQ-9) to assess the prevalence of depression. Association of depression with respect to demographic and disease-related factors were also assessed. Data were coded and analysed using SPSS v22. Results: A total of 144 patients suffering from HIV were participated in this study. Among this selected participants, 47% were female. The mean age of participants was 38.8 years (SD=11.4). Depression was prevalent in 57% (95% CI: 48.91 to 65.09) of patient participated in the study and was highly prevalent in female (66%). Prevalence of depression was higher in patient belongs to upper lower and lower socioeconomic class. More than a quarter 28% (95% CI: 21.56 to 36.44) of respondents had mild depression, while 29% (95% CI: 21.99 to 36.41) of participants were suffering from moderate to severe depression. Prevalence of depression was found to be significantly associated with lower socioeconomic class (OR 2.458, 95% CI 1.081–5.592; p < 0.05 ). Conclusion: Depression is highly prevalent among HIV-positive patients in Bihar region. Higher odds of prevalent depression were observed in lower socioeconomic class. Nearly 30% HIV positive patients were suffering from moderate to severe depression.